Over-Expression and Prognostic Significance of HHLA2, a New Immune Checkpoint Molecule, in Human Clear Cell Renal Cell Carcinoma - Zhang, Zhen; Liu, Jinyan; Zhang, Chaoqi; Li, Feng; Li, Lifeng; Wang, Dan; Chand, Damini; Guan, Fangxia; Zang, Xingxing; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2020)
HHLA2, a newly identified B7 family member, regulates T cell functions. However, the expression and prognostic value of HHLA2 in solid tumors is ill defined. This study aimed to reveal the expression landscape of HHLA2 in various solid tumors, and to evaluate its prognostic value in kidney clear cell carcinoma (KIRC). Using the TCGA database we investigated the expression pattern of HHLA2 across 22 types of cancer. Immunohistochemistry (IHC) was performed to detect the protein expression of HHLA2 and CD8. KIRC-specific findings were further analyzed with R software and the prognostic value was validated on tissue microarrays. HHLA2 was widely expressed in cancers at both the mRNA and protein levels. Among all the tumors, KIRC showed the highest transcript level of HHLA2. Furthermore, the level of HHLA2 was significantly higher in tumor tissues than that of matched normal samples, which was recapitulated by both TCGA and IHC data. HHLA2 was also positively correlated with survival time in KIRC from TCGA and clinical data. In addition, ROC data showed prognostic value of HHLA2 for KIRC patients in the TCGA. Additionally, HHLA2 was positively correlated with immune-related genes, and HHLA2 and CD8 had a consistent expression trend in KIRC tumor samples. In conclusion, HHLA2 was highly expressed in KIRC and its high level predicted a favorable survival outcome, which highlighted that it may work as a potential target for KIRC therapy.